2013
DOI: 10.1111/jir.12035
|View full text |Cite
|
Sign up to set email alerts
|

Are cervical and breast cancer screening programmes equitable? The case of women with intellectual and developmental disabilities

Abstract: Background Effective cancer screening must be available for all eligible individuals without discrimination. Lower rates of cervical and breast cancer screening have been reported in certain groups compared with women from the general population, such as women with intellectual and developmental disabilities (IDD). Research on the factors explaining those observed differences is crucial to determine whether practices are unfair and could be improved. The aim of this population‐based study was to describe cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 28 publications
2
65
1
4
Order By: Relevance
“…They include physical disability, level of intellectual disability, ill health of the woman or carer, moving house, access issues such as transport, capacity to consent, fear of the procedure and embarrassment. These are consistent with those found in the general population (Cobigo et al ., ; Isaacs, ; Lalor & Redmond, ; Parish et al ., ; Pehl & Hunt, ; Poynor, ; Sullivan et al ., , ; Svien et al ., ). To address low uptake, there have been many reported education and training initiatives for health and social care staff to encourage women with intellectual disabilities to attend screening (for a comprehensive review, see Willis et al ., ).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…They include physical disability, level of intellectual disability, ill health of the woman or carer, moving house, access issues such as transport, capacity to consent, fear of the procedure and embarrassment. These are consistent with those found in the general population (Cobigo et al ., ; Isaacs, ; Lalor & Redmond, ; Parish et al ., ; Pehl & Hunt, ; Poynor, ; Sullivan et al ., , ; Svien et al ., ). To address low uptake, there have been many reported education and training initiatives for health and social care staff to encourage women with intellectual disabilities to attend screening (for a comprehensive review, see Willis et al ., ).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The present authors have not identified other studies reporting the management of long‐term conditions in this population. What is clearer is that lower rates of cervical screening and mammography are reported for women with intellectual disabilities compared with the general population (Cobigo et al., ; Kerr, Richards, & Glover, ; Osborn et al., ; Reynolds, Stanistreet, & Elton, ; Wood, ), although mammography screening was found to be comparable to levels in the general population in one study (Biswas, Whalley, Foster, Friedman, & Deacon, ).…”
Section: Introductionmentioning
confidence: 96%
“…A recent multi-country study showed that disability was consistently more prevalent in the poorest than richest quintiles. 46 In their population-based study, Cobigo and colleagues 47 showed that the proportion of Ontario women with intellectual and developmental disabilities who were not screened for cervical cancer was nearly twice that of women without these disabilities. Multimorbidity has been strongly associated with preventable hospital admissions, and this risk is exacerbated by socioeconomic deprivation.…”
Section: Cmaj Openmentioning
confidence: 99%